THE STUDENTS’ NEWS WRITING DIFFICULTIES BASED ON COGNITIVE PROCESS - Agus Wismanto; Zainal Arifin; Siti Fatimah (ETERNAL (English Teaching Journal), 2022)
What are the students' news writing challenges in the fourth semester of Grade E, according to this study's major issue? And what are the cognitive process-based characteristics that affect the students' difficulty with news writing in the fourth semester of grade E? The goal was to determine the students' news writing challenges in the fourth semester of Grade E and the factors affecting those challenges based on the students' cognitive processes at that time. The focus of the study was the fourth semester's twenty-two student population. The Qualitative Research Method was employed in this study. The information was acquired through observation, document (news articles written by students), and interview. The results demonstrated that there are two categories of students who have trouble pre-writing and pre-drafting a news article. The outcome showed there are nine students.